Análise comparativa da sustentabilidade do cultivo de camarão marinho nos sistemas semi-intensivo (tradicional) e superintensivo (com reuso de água e uso de bioflocos-BFT) utilizados no Brasil - Matias, João Felipe Nogueira (2018)
Actually, the production systems have generated huge socio-environmental imbalances across the planet. However, organizations have been increasingly preoccupied with these imbalances and have been searching for productive systems that operate under the economic, social and environmental dimensions of sustainability, the Triple Bottom Line. In the scope of agribusiness, one of the activities that has been showing the greatest development in the world is the production of seafood. This production can be done by fishing or by farming (aquaculture). The cultivation of aquatic organisms (aquaculture) is already responsible for 53% of the world consumption of seafood. In Brazil, it is has been gaining more and more importance in animal production in all region across the country. In Northeast region of Brazil, fish and shrimp farming are the two most important branches of aquaculture. The cultivation of marine shrimps in the semi-intensive system is the traditional way of using in our country. The use of this system has a historical of socio-environmental conflicts and recently has had serious problems with diseases, which caused a loss of almost 50% in the national production. In this way, new production systems must be tested and the superintensive system with water reuse and biofloc use (BFT) has been getting around the world as an alternative to the traditional system. In this dissertation we performed the sustainability analysis of marine shrimp culture in these two systems. The sustainability indicators matrix, methodology adopted by Bezerra (2017) was used to calculate the subindex of economic, social and environmental sustainability; which allowed to calculate the general index of sustainability - IGS from the marine shrimp culture in a superintensive system (BFT Technology) and thus, to made the comparison between the two systems. It was verified that the subindexes and IGS of the superintensive system presented, in general, higher values than those of the semi-intensive system calculated by Bezerra (2017); which allowed us to conclude that the cultivation of marine shrimps in the superintensive system with water reuse and bioflocosis (BFT) is more sustainable than the culture in the semi-intensive one.